CHARACTER EDUCATION IN BANJARAN BIMA PLAY AND ITS IMPLICATION IN EDUCATION - Dwijonagoro, Suwarna; Meilawati, Avi; Nurhidayati, Nurhidayati; Wulan, Sri Hertanti (Jurnal Pendidikan Karakter, 2019)
Character education is very essential. Good character brings peace, happiness and peace of mind, both personally and socially, even for the nation. Character education reflection is shown in many puppet shows. Wayang as a spectacle and guidance. Wayang as a spectacle is for entertainment, while as a guidance is a vehicle for character education. Which is indeed full of character education. The data source of this research was "Banjaran Bima Play" in the video of Ki Seno Nugroho's puppet show, and is done by exploring and collaborating character education in the Banjaran Bima puppet play and its implications in education. This research used an instrument in the form of data cards. Data collection was done through the stages of observing, transcribing, identifying, and coding. The data validity was established through in-depth observation, repeated studies, extended participation, peer discussions, and source triangulation. Data analysis technique used the steps of classification, description, interpretation, elaboration, and conclusion. The results of the study show the character of (1) Godhead, (2) obedient to teachers and parents, (3) nationalism, (4) integrity, (5) responsibility, (6) discipline, (7) respect for others, ( 8) independent, (9) mutual cooperation, (10) hard worker, and (11) smart. These various characters can be implicated in the field of education, both at the education center (informal, formal and non-formal) and at every level of education (elementary school to university). This is evidenced that these characters are always contained in the Education Curriculum in Indonesia since 1947 to 2013 with various developments. Keywords: character, puppet, Banjaran Bima, spectacle, guidance,  PENDIDIKAN KARAKTER DALAM LAKON BAJARAN BIMA DAN IMPLIKASINYA  DALAM PENDIDIKAN Pendidikan karakter amatlah penting. Karakter baik membawa kedamaian, kebahagiaan, dan ketenteraman jiwa, baik secara personal maupun sosial, bahkan bagi bangsa dan negara. Pendidikan karakter banyak ditentukan dalam pertunjukan wayang. Wayang sebagai tontonan dan tuntunan. Sebagai tontonan wayang untuk hiburan, sebagai tuntutan wayang sebagai wahana pendidikan karakter.  Sumber data penelitian adalah Lakon Banjaran Bima dalam video pagelaran wayang oleh Ki Seno Nugroho dengan mengeksplorasi dan mengalobari pendidikan karakter dalam lakon wayang  Banjaran Bima dan implikasinya pendidikan. Penelitian ini menggunakan instrumen yang berupa kartu data. Pemerolehan data melalui tahapan mengamati, mentranskripsi, mengidentifikasi, dan kodifikasi. Keabsahan data menggunakan pengamatan yang mendalam/cermat, kajian berulang, perpanjangan keikutsertaan, diskusi teman sejawat, triangulasi sumber.  Analisis data menggunakan langkah klasifikasi, deskripsi, interpretasi, elaborasi, dan inferensi. Hasil penelitian menunjukkan karakter (1) Berketuhanan, (2) patuh pada guru dan orang tua, (3) nasionalisme, (4) integritas, (5) bertanggung jawab, (6) kedisiplinan, (7) menghormati orang lain, (8) mandiri, (9) gotong royong, (10) pekerja keras, dan (11) cerdas. Berbagai karakter tersebut dapat diimplikasikan dalam bidang pendidikan, baik pada tripusat pendidikan (informal, formal, dan nonformal) maupun pada setiap jenjang pendidikan (Sekolah Dasar  hingga Perguruan Tinggi). Hal ini dibuktikan bahwa karakter-karakter tersebut selalu termuat dalam Kurikulum Pendidikan di Indonesia semenjak 1947 hingga 2013 dengan mengalami berbagai perkembangan. Kata kunci: karakter, wayang, Banjaran Bima, tontonan, tuntunan